2018
DOI: 10.1111/apt.14480
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: tofacitinib and biologics for moderate‐to‐severe ulcerative colitis—what is best in class?

Abstract: Double-blind placebo controlled clinical trials remain the most important method of evaluating the safety and efficacy of a drug.However, these are very costly to run and drug license holders do their major trials largely for regulatory bodies. With the proliferation of biologic therapies for the treatment of inflammatory bowel diseases, it is reasonable to ask which drug is the most effective for a particular clinical problem. Prospective double-blind head-to-head clinical trials are the best ways to resolve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On the other hand, the search for inflammatory markers in colonic disorders can easily raise concerns regarding doctor–patient relationship. For instance, prescription of the anti-inflammatory aminosalycilic acid (5-ASA) can make an IBS patient believe that the diagnosis of full-blown IBD had been originally missed; moreover, UC patients, if offered to participate in a trial with the anti-STAT molecule tofacitinib,57 may suspect being offered a modern expensive version of a cortisone drug.…”
Section: Study Conceptmentioning
confidence: 99%
“…On the other hand, the search for inflammatory markers in colonic disorders can easily raise concerns regarding doctor–patient relationship. For instance, prescription of the anti-inflammatory aminosalycilic acid (5-ASA) can make an IBS patient believe that the diagnosis of full-blown IBD had been originally missed; moreover, UC patients, if offered to participate in a trial with the anti-STAT molecule tofacitinib,57 may suspect being offered a modern expensive version of a cortisone drug.…”
Section: Study Conceptmentioning
confidence: 99%
“…Tofacitinib is a novel treatment option for UC, pending review by the US Food and Drug Administration (FDA), the European Medicines Agency (EMA), and other international regulators . It is very interesting in our study results that the efficacy of tofacitinib could not be shown to be different than that of approved biologic therapies, though—as correctly Dr. Tsai points out—tofacitinib appears to be “slightly sub‐par” to infliximab and vedolizumab in all efficacy comparisons. Nevertheless, given that its oral administration may increase treatment adherence and improve quality of life in patients distressed by the long‐term need for injections or infusions, tofacitinib could be well integrated into clinical practice …”
mentioning
confidence: 70%
“…We thank Dr. Tsai for his editorial on our publication . We conducted a systematic review of randomised controlled trials assessing tofacitinib and approved biologics (infliximab, adalimumab, golimumab, vedolizumab) as induction and/or maintenance therapies for adult patients with moderate‐to‐severe ulcerative colitis (UC), who were not previously exposed to tumour necrosis factor antagonists.…”
mentioning
confidence: 99%
“…The undecapeptide Cyclosporin [18] and the anti-TNF monoclonals [19] represent the new remedies for the acute IBD presentations. The very new strategy designed to inhibit the bulk of the immune responses promoted by activation of the Janus Kinases, is the design that pivots on the molecule "Tofacitinib", a JAK inhibitor that is active on a number of pro-inflammatory cytokines [20].…”
Section: Treatment Arsenalmentioning
confidence: 99%